THE IMPACT OF THE BEIJING OLYMPIC SPONSORSHIP PROGRAM ON ANNUAL REPORT SOCIAL DISCLOSURE OF LOCAL SPONSORS - Christopher, Theo; Hu, Juncheng (The journal of contemporary issues in business and government, 2010)
The aim of this study is to utilise legitimacy theory to explain the impact of the Beijing Olympic Sponsorship Program on annual report social disclosures including event-related disclosure of local sponsor companies for this legitimacy enhancing and maintaining positive event. The study is concerned with examining whether the arguments developed in relation to legitimacy repairing negative events explain corporate disclosure response to these legitimacy maintaining and enhancing positive events. The findings indicate that sponsors disclosed more social and event-related information but this was not the case for non-sponsors. It was also found that sponsors disclose more event-related information than non-sponsors but not in relation to overall disclosure. This result provides support for legitimacy theory for these legitimacy maintaining and enhancing positive events but is not entirely identical to the findings for legitimacy repairing associated with negative events.